2020
DOI: 10.1136/bmjgh-2020-003304
|View full text |Cite
|
Sign up to set email alerts
|

Community interventions with women’s groups to improve women’s and children’s health in India: a mixed-methods systematic review of effects, enablers and barriers

Abstract: IntroductionIndia is home to over 6 million women’s groups, including self-help groups. There has been no evidence synthesis on whether and how such groups improve women’s and children’s health.MethodsWe did a mixed-methods systematic review of quantitative and qualitative studies on women’s groups in India to examine effects on women and children’s health and to identify enablers and barriers to achieving outcomes. We searched 10 databases and included studies published in English from 2000 to 2019 measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 105 publications
(100 reference statements)
1
19
0
Order By: Relevance
“…Impact evaluations and observational studies indicate some improvements in health behaviors among SHG members through layered interventions. 1,2,25,26 However, global evidence syntheses on women's groups have identified significant gaps in our understanding of how these interventions work-who participates, for how long, what do they do, and how often. 27 Understanding the implementation intensity of these interventions is critical to identifying implementation features specific to women's groups that influence effectiveness, along with transferability and scalability in different settings.…”
mentioning
confidence: 99%
“…Impact evaluations and observational studies indicate some improvements in health behaviors among SHG members through layered interventions. 1,2,25,26 However, global evidence syntheses on women's groups have identified significant gaps in our understanding of how these interventions work-who participates, for how long, what do they do, and how often. 27 Understanding the implementation intensity of these interventions is critical to identifying implementation features specific to women's groups that influence effectiveness, along with transferability and scalability in different settings.…”
mentioning
confidence: 99%
“…We developed our typology to explain clear differences in health impact by intervention type in a recent systematic review of women's group interventions in India. 7 Importantly, our review highlighted that different types of women's groups, such as microfinance-oriented selfhelp groups or sex workers collectives, can use different intervention ideal types depending on the context. For example, a government-run self-help group programme in Bihar, India, has implemented a classroom intervention to improve dietary diversity, 38 but also a club intervention to reduce gender-based violence 64 and a collective approach with participatory learning and action.…”
Section: Resultsmentioning
confidence: 99%
“…We recently did a systematic review of the impact of women's groups interventions on health in India which found a clear difference in health impact by intervention type, with interventions building community capacity more likely to achieve changes in population-level health outcomes than those simply offering information. 7 Our present paper builds on this review to offer conceptual tools for thinking through observed differences in health impacts by type of group intervention. We introduce a typology of group interventions and argue that implicit assumptions underpinning different types of intervention matter for their likely health impact.…”
Section: Introductionmentioning
confidence: 99%
“…We build on previous reviews by (1) focusing on the combined effect of group-based economic and health programmes, as distinct from previous reviews that examined the health impacts of joining a microfinance-based group with or without layering 4 or non-group-based microfinance interventions 5 and (2) including studies across all LMICs rather than a specific region. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the protocol, following Preferred Reporting Items for Systematic Review and Meta-analysis Protocols guidelines, 10 for a review we will conduct, which aims to address this gap through synthesising quantitative and qualitative evidence on the health effects of combined group-based economic and health interventions and implementation factors that contributed to achieving intended outcomes. We aim to answer two primary questions: (1) What is the effect of combined economic and health, nutrition and/or sanitation interventions delivered through women’s groups on health outcomes among women and children in LMICs, compared with single-purpose, non-layered (ie, only economic or only health) interventions with women’s groups or to no group intervention, and (2) what factors related to intervention content, context and implementation processes are enablers or barriers to achieving health outcomes?…”
Section: Introductionmentioning
confidence: 99%